Correlation of Hypoechoic Lesions in Trans-rectal Ultrasound of Prostate with Histopathology in Prostate Cancer - Chataut, Dinesh; Basnet, Babin; Lohani, Benu; Suwal, Sundar; Paudel, Sharma; Kayastha, Prakash (Journal of Institute of Medicine Nepal, 2020)
Introduction Prostate cancer is one of the most common cancer in elderly male. Suspicion of prostate cancer is based on increased Prostate Specific Antigen (PSA) level and abnormal digital rectal examination (DRE) findings. Transrectal ultrasonography (TRUS) can detect and localize hypoechoic lesions in prostate which are considered as suspicious for malignancy. TRUS can also guide for prostate biopsy, which is the gold standard for diagnosis of prostate cancer. The study was aimed to find out TRUS findings in suspected prostate cancer patients and correlate these findings with histopathological findings. Methods Prospective study was done in 66 males of age >40 years, sent for prostate biopsy in suspicion for prostate cancer (PSA >4 ng/ml, and/or abnormal DRE findings). Prostate was evaluated with TRUS and subsequently underwent TRUS guided six core biopsy of prostate. Total 396 cores of biopsy were taken. Histopathology reports were collected and correlated with the TRUS findings. Results Twenty three patients were positive for prostate cancer and 14 of them showed hypoechoic lesions in TRUS. Total 81 suspicious hypoechoic lesions were seen in prostate of all the patients and among them 42 lesions matched with histopathology report for cancer. Cancerous focus detection rate of TRUS was 51.85%. Conclusion TRUS is a supplementary tool in diagnosis of prostate cancer, however when used alone it has less sensitivity for detection of prostate cancer.